2015
DOI: 10.14310/horm.2002.1633
|View full text |Cite
|
Sign up to set email alerts
|

The Sertoli cell as the orchestra conductor of spermatogenesis: spermatogenic cells dance to the tune of testosterone

Abstract: Spermatogenesis is contingent upon hormones and growth factors acting through endocrine and paracrine pathways either in vivo or in vitro. Sertoli cells (SCs) furnish essential factors for the successful advancement of spermatogenesis and spermiogenesis. Moreover, receptors for follicle stimulating hormone (FSH) and testosterone, which are the main hormonal regulators of spermatogenesis, are identified on SCs. Testosterone, FSH and luteinizing hormone are known to determine the destiny of germ cells and in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 209 publications
1
42
0
Order By: Relevance
“…Sertoli cells are localized in the seminiferous epithelium, in which they play a dual role. Sertoli cells have the ability of rapidly proliferate in pre‐pubertal period, and then they provide nutrients and regulators to support spermatogenesis after they lose the ability to proliferate in adult testis (Chojnacka, Zarzycka, & Mruk, ; Dimitriadis et al, ; Gerber, Heinrich, & Brehm, ). Recent studies have reported that the number of Sertoli cells in the seminiferous epithelium determines the number of germ cells that will be present in adult testicular tissue (Rebourcet et al, ), as each Sertoli cell supports only a limited number of germ cells (Johnson, Thompson, & Varner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sertoli cells are localized in the seminiferous epithelium, in which they play a dual role. Sertoli cells have the ability of rapidly proliferate in pre‐pubertal period, and then they provide nutrients and regulators to support spermatogenesis after they lose the ability to proliferate in adult testis (Chojnacka, Zarzycka, & Mruk, ; Dimitriadis et al, ; Gerber, Heinrich, & Brehm, ). Recent studies have reported that the number of Sertoli cells in the seminiferous epithelium determines the number of germ cells that will be present in adult testicular tissue (Rebourcet et al, ), as each Sertoli cell supports only a limited number of germ cells (Johnson, Thompson, & Varner, ).…”
Section: Introductionmentioning
confidence: 99%
“…FSH, whose receptor (FSH-r) is located exclusively on SC, is the principal regulator of SC function and modulates testosterone (T) production, through SC factors with the synergistic contribution of LC to attain correct spermatogenesis. In fact, there is clear evidence that both FSH and T are essential for adequate spermatogenesis 6. In particular, FSH is critical in the early stages (alone and in cooperation with testosterone) and testosterone is essential for the final stages of spermatogenesis, involving the production of elongated spermatids, considered the main limiting factors for in vitro spermatogenesis 7891011.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, FSH is critical in the early stages (alone and in cooperation with testosterone) and testosterone is essential for the final stages of spermatogenesis, involving the production of elongated spermatids, considered the main limiting factors for in vitro spermatogenesis 7891011. Thus, Dimitriadis et al 6. emphasized this concept in a recent study.…”
Section: Introductionmentioning
confidence: 99%
“…Sertoli cells, localized in seminiferous epithelium, have the ability to rapid proliferate during the pre‐pubertal period as the basic structure of the mammalian testicular tissue. However, Sertoli cells also provide the nutrients and regulatory factors for supporting all phases of germ cell development and maturity when they lose their proliferative ability in mature testis (Chojnacka, Zarzycka, & Mruk, ; Dimitriadis et al., ; Gerber, Heinrich, & Brehm, ). Accumulating evidence has shown that autophagy can guarantee the normal functional role to support germ cell development and maturity through degradation of the PDLIM1 protein or degradation of ingested cell‐derived substrates (Liu et al., ; Yefimova et al., ).…”
Section: Introductionmentioning
confidence: 99%